2000
DOI: 10.1029/2000wr900092
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic model for posttillage soil pore space evolution

Abstract: Abstract. Tillage operations disrupt surface layers of agricultural soils, creating a loosened structure with a substantial proportion of interaggregate porosity that enhances liquid and gaseous exchange properties favorable for plant growth. Unfortunately, such desirable soil tilth is structurally unstable and is susceptible to change by subsequent wetting and drying processes and other mechanical stresses that reduce total porosity and modify pore size distribution (PSD). Ability to model posttillage dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 35 publications
4
94
0
1
Order By: Relevance
“…3). Similarly to that reported by Calonego and Rosolem (2011), an increase of the S Dexter index was observed after tillage As reported by several authors (Schwen et al, 2011a(Schwen et al, , 2011bOr et al, 2000;Leij et al, 2002;Moret-Fernández et al, 2013), the rainfall was the main factor that conditions the changes in the θ(ψ) parameters (Table 2, figures 5 and 7). These changes should be related to the wetting process of the freshly tilled soil that promotes the disintegration and deformation of the more unstable soil aggregates (Shiel et al, 1988;Day and Holmgren, 1952).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…3). Similarly to that reported by Calonego and Rosolem (2011), an increase of the S Dexter index was observed after tillage As reported by several authors (Schwen et al, 2011a(Schwen et al, , 2011bOr et al, 2000;Leij et al, 2002;Moret-Fernández et al, 2013), the rainfall was the main factor that conditions the changes in the θ(ψ) parameters (Table 2, figures 5 and 7). These changes should be related to the wetting process of the freshly tilled soil that promotes the disintegration and deformation of the more unstable soil aggregates (Shiel et al, 1988;Day and Holmgren, 1952).…”
Section: Discussionsupporting
confidence: 66%
“…Although PSD does not provide direct information about the porosity, it gives a measure of the relative abundance of pore size (Or et al, 2000).…”
Section: Field and Laboratory Measurementsmentioning
confidence: 99%
“…Following the study of Hara (1984), Or et al (2000) and Leij et al (2002) proposed using the advection-dispersion equation, which is a special form of the Fokker-Planck equation, for stochastic modeling of changes in soil pore size distributions associated with tillage operations. In the simplest case for the application of this equation to the change in pore size distribution as a result of structure development, the following simple growth equation for an individual pore size r may be used:…”
Section: Change In Water Retention Parametersmentioning
confidence: 99%
“…These differences can be attributed not only to vehicular traffic at the Field site but also to tillage. Rousseva et al (1988) and Or et al (2000) found that after tillage operations, cycles of wetting and drying might cause an increase in soil bulk density due to reconsolidation. The differ- Effects of management and depth on porosity for selected pore size classes: (a) macropores (>1,000 μm diameter), (b) coarse mesopores (60 to 1,000 μm diameter), (c) fine mesopores, (10 to 60 μm diameter), and (e) micropores (<10 μm diameter ences in bulk density due to soil depth were mainly due to differences in structure and texture.…”
Section: Macroporositymentioning
confidence: 99%